Intimate partner physical violence among women in Shimelba refugee camp, northern Ethiopia - Feseha Girmatsion; G/mariam Abebe; Gerbaba Mulusew (BMC, 2012)
Abstract Background Domestic violence has unwanted effects on the physical and psychological well-being of women, which have been recognized globally as an important public health problem. Violence perpetrated by intimate partner is one form of domestic violence, a serious human rights abuse and a public health issue, among refugees owing to its substantial consequences for women's physical, mental and reproductive health problems. Because the incidents are under-reported, the true scale of the problem is unknown and unexamined among refugee women in Ethiopia. Thus, this study aim to assess the magnitude of intimate partner physical violence and associated factors among women in Shimelba refugee camp, Northern Ethiopia. Methods A community-based cross-sectional study was conducted among a sample of 422 refugee women from March to April 2011. A simple random sampling method was used to select the study subjects from seven zones of the refugee camp. Census was done to identify all households with women having an intimate partner. A pre-tested interviewer guided structured questionnaire was used for data collection. Data were entered, cleaned and analyzed using SPSS software version 16.0. Descriptive, bivariate and multivariate logistic regression analyses were done where applicable. A p-value less than 0.05 with 95% CI were set and used as a cut-off point to examine the statistical association between the explanatory and outcome variables. Results The prevalence of physical violence in the last 12 months and lifetime were 107(25.5%) and 131(31.0%) respectively. The commonest forms of physical violence reported included slapping 101(61.6%) and throwing objects 32(19.5%). Significant risk factors associated with experiencing physical violence were being a farmer (AOR = 3.0[95%CI: 1.7, 5.5]), knowing women in neighborhood whose husband to beat them (AOR = 1.87[95%CI: 1.0, 3.5]), being a Muslim (AOR = 2.4 [95%C.I: 1.107, 5.5]), and having a drunkard partner (AOR = 2.1[95%C.I:1.0, 4.5]). Conclusions Intimate partner physical violence was found to be high and a serious problem among women in Shimelba refugee camp. Multifaceted interventions such as male counseling, increasing awareness on the consequences of intimate partner violence and the effect of substance use like alcohol will help to reduce intimate partner violence.